2017
DOI: 10.3390/min7030042
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Reduced Acid and Metalliferous Drainage by Pyrite Surface Passivation

Abstract: Acid and metalliferous drainage (AMD) is broadly accepted to be a major global environmental problem facing the mining industry, requiring expensive management and mitigation. A series of laboratory-scale kinetic leach column (KLC) experiments, using both synthetic and natural mine wastes, were carried out to test the efficacy of our pyrite passivation strategy (developed from previous research) for robust and sustainable AMD management. For the synthetic waste KLC tests, initial treatment with lime-saturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…SEM-EDS analysis suggested that pyrite surfaces (50.1 S, 44.9 Fe, 5.0 O; all in wt %) from the control were possibly covered to some degree with iron (oxy)hydroxide, and that pyrite (47.4 S, 34.5 Fe, 14.9 O, 3.2 Si; all in wt %) from lime + silicate + cover may be coated by silicate-doped iron (oxy)hydroxide layers. These observations are largely consistent with the preposition that pyrite surfaces may be passivated by silicate-stabilised surface iron (oxy)hydroxide layers under alkaline pH conditions in this study [3,6,13]. Further analysis, such as focused ion beam SEM and transmission electron microscopy, will be carried out to examine the nature of these oxidation layers.…”
Section: Pyrite Morphologysupporting
confidence: 65%
See 1 more Smart Citation
“…SEM-EDS analysis suggested that pyrite surfaces (50.1 S, 44.9 Fe, 5.0 O; all in wt %) from the control were possibly covered to some degree with iron (oxy)hydroxide, and that pyrite (47.4 S, 34.5 Fe, 14.9 O, 3.2 Si; all in wt %) from lime + silicate + cover may be coated by silicate-doped iron (oxy)hydroxide layers. These observations are largely consistent with the preposition that pyrite surfaces may be passivated by silicate-stabilised surface iron (oxy)hydroxide layers under alkaline pH conditions in this study [3,6,13]. Further analysis, such as focused ion beam SEM and transmission electron microscopy, will be carried out to examine the nature of these oxidation layers.…”
Section: Pyrite Morphologysupporting
confidence: 65%
“…Quartz, K-feldspar and chlorite (Geo Discoveries, New South Wales, Australia) were crushed, pulverised and dry-sieved to <4 mm size for the KLC experiments as per Qian et al [6]. Setup and daily operation for the KLCs were based on Smart et al [7], except that different solutions were used for watering/flushing, and KLCs other than the control were flushed with lime-saturated water (supernatant after dissolving >95% pure Ca(OH) 2 in Milli-Q water until saturation; alkalinity: ≈1900 mg CaCO 3 L −1 ) after flush 1.…”
Section: Kinetic Leach Columns (Klc)mentioning
confidence: 99%
“…Acid mine drainage (AMD) is considered to be a global environmental problem faced by mining industries due to the biological oxidation of sulfidic minerals (Johnson and Hallberg, 2005; Neculita and Zagury, 2008; Qian et al, 2017). Owing to its highly toxic nature manifested through acidic pH, elevated levels of heavy metals and sulfate, AMD is not only a threat to aquatic and terrestrial ecosystems but considered to be a major contributor in long term degradation of environmental quality (Johnson and Hallberg, 2005; Chandra and Gerson, 2010; Hallberg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For these last several decades, AMD has been treated properly in Japan and has not caused severe pollution. However, since our results of the statistical calculation (details are shown below) suggested that some mines have required AMD treatment for over 150 years [13,14] and other groups suggested that more than 1000 years of treatment will be necessary [15] in the current situation, more sustainable treatment to reduce both AMD generation [16,17] and treatment cost [18] is needed. To reduce the treatment cost of the addition of chemicals and of sludge generation, for example, a passive treatment that utilizes the natural environment of mines, such as topography, plants, and microorganisms, has attracted attention as a sustainable AMD treatment based on new concepts [19][20][21].…”
Section: Introductionmentioning
confidence: 86%